1984
DOI: 10.3758/bf03333869
|View full text |Cite
|
Sign up to set email alerts
|

The disappearance of dichoptically presented real and subjective contours

Abstract: An underlying question for much of the research on subjective contours is the degree to which central and peripheral mechanisms contribute to their perception. The luminous design technique described by McKinney (1963McKinney ( , 1966 provides an appropriate tool for this investigation. He found that when luminous drawings are observed under dim illumination, they fragment, 433

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1988
1988
1994
1994

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…First, von der Heydt, Peterhaus, and Baumgartner (1984) clearly demonstrate that illusory contours are cortical in origin. Halpern and Warm (1984) generated subjective contours with dichoptic presentations of their luminous figures. These contours faded but the illusory contour persisted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, von der Heydt, Peterhaus, and Baumgartner (1984) clearly demonstrate that illusory contours are cortical in origin. Halpern and Warm (1984) generated subjective contours with dichoptic presentations of their luminous figures. These contours faded but the illusory contour persisted.…”
Section: Discussionmentioning
confidence: 99%
“…These studies indicate that persistence lasts beyond the visible persistence of the inducing stimulus as now found. Using luminous target fading of a subjective contour, Halpern and Warm (1981, 1984) report "when the inducing areas disappear, the subjective contours remain visible for a brief period via sensory and/or cognitive persistence" (1981, p. 232). They conclude, "In the jargon of information processing, top-down contours are less prone to disappearance than bottom-up ones" (1984, p. 436).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown . that the performance of subjects on a variety of perceptual tasks improves as a function of task experience (see Gibson,1,969).…”
Section: Discussionmentioning
confidence: 99%
“…Frisby and Clatworthy pointed to the work of neurophysiologists Rodieck and Stone (1965) as salvaging a possible brightness contrast explanation of the illusory circle seen in Figure 2 (top panel). 1 Frisby and Clatworthy noted several properties of SCs that would seem to indicate an important role for brightness contrast in their perception. For example, SCs are usually strongest when black and white offset each other; offsetting gray and white attenuates the strength of the illusion.…”
Section: Lateral Inhibitory Brightness Contrastmentioning
confidence: 99%
“…For subjective contours, disappearances occurred primarily in the physically present inducing areas, while the subjective edges remained visible, and there were fewer whole figure disappearances. In a later study, Halpern and Warm (1984) demonstrated that subjective contours could be rendered more stable than real contours under dichoptic viewing conditions (different portions of a figure are presented to each eye) wherein figure completion must be accomplished postretinally. The studies of Warm (1980, 1984) reveal some of the characteristics of fragmentation in illusory figures and, given the outcome of the dichoptic experiment, suggest that fragmentation of subjective contours may be more centrally determined than the fragmentation of real contours.…”
mentioning
confidence: 99%